ANALISIS LAPORAN ARUS KAS SEBAGAI DASAR PENGUKURAN LIKUIDITAS PADA PERUSAHAAN â€œUNICAREâ€ CABANG MANADO - Mogi, Chintia Debby; Poputra, Agus; Alexander, Stanly W. (Universitas Sam Ratulangi, 2016)
Cash flow statement is a summary of financial transactions related to cash, which depicts the historical changes in cash and cash equivalents classified into operating, investing their and funding during the period. Liquidity is an indicator of the kemampuam a company to pay all short-term financial obligations at maturity using liquid assets available. Therefore, cash flow greatly affect the measurement of liquidity, which in paying a short-term financial obligations indispensable good cash flow. Cash is the most dominant current assets in measuring the company's liquidity.